The Effect of Sintering Time on Surface Morfology of Pb-Doped Bi-2223 Oxides Superconductors Prepared by the Solid State Reaction Methods at 840 oC - Evi Yufita; Nurmalita . (Journal of Aceh Physics Society, 2016)
This study was investigating the effect of sintering time (30 h, 32 h, and 34 h) on surface morphology of PbdopedBi-2223 oxides of superconductors prepared by the solid-state reaction method at 840 oC. Thesuperconductor was characterized by X-Ray Diffraction (XRD) and Scanning Electron Microscopy (SEM).In the present study, phase purity, volume fraction, surface morphology, texturing, crystallinity, grainconnectivity and grain size of the bulk samples are found and compared with each other. The enhancementin the sintering time is confirmed that it will decrease Bi-2223 phase fraction and increase the impurity ofthe samples. SEM images shows that the sample has the best crystallinity, grain connectivity and largestgrain size. Based on the present results, it is conclude that the surface morphological is improving with theincreasing of the sintering time.